2007
DOI: 10.1016/j.immuni.2006.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein gp96 Is a Master Chaperone for Toll-like Receptors and Is Important in the Innate Function of Macrophages

Abstract: gp96 is an endoplasmic reticulum chaperone for cell-surface Toll-like receptors (TLRs). Little is known about its roles in chaperoning other TLRs or in the biology of macrophage in vivo. We generated a macrophage-specific gp96-deficient mouse. Despite normal development and activation by interferon-gamma, tumor necrosis factor-alpha, and interleukin-1beta, the mutant macrophages failed to respond to ligands of both cell-surface and intracellular TLRs including TLR2, TLR4, TLR5, TLR7, and TLR9. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
463
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 409 publications
(483 citation statements)
references
References 51 publications
20
463
0
Order By: Relevance
“…Recently, Unc93B1, a multitransmembrane ERresident protein has been shown to associate with and deliver TLR7/9 from the ER to endosomes, where TLR7/9 recognizes their ligands [40]. In addition, gp96, an ER-resident HSP, has been shown to be a master immune chaperone for both cell surface and intracellular TLRs, including TLR1, 2, 4, 5, 7, and 9 [26]. In this study, we clarified that endosomal TLR7 and TLR9 are functionally dependent on the cytosolic chaperone Hsp90.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Unc93B1, a multitransmembrane ERresident protein has been shown to associate with and deliver TLR7/9 from the ER to endosomes, where TLR7/9 recognizes their ligands [40]. In addition, gp96, an ER-resident HSP, has been shown to be a master immune chaperone for both cell surface and intracellular TLRs, including TLR1, 2, 4, 5, 7, and 9 [26]. In this study, we clarified that endosomal TLR7 and TLR9 are functionally dependent on the cytosolic chaperone Hsp90.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yang et al have shown that gp96 was required to activate TLR7 and TLR9 in response to ligand stimulation [26]. Thus, gp96 acts as a master chaperone for TLR7 and TLR9 and it is indispensable for proper conformation of TLR7 and TLR9 in collaboration with PLAT4A [27].…”
Section: Hsp90 Is Essential For Cpg-a-mediated Tlr9 Translocation To mentioning
confidence: 99%
“…Further analysis of this mutant revealed that the major defect in this cell was in its cell surface expression of TLRs, revealing a hitherto unknown role for Gp96 in inserting the TLR proteins into the plasma membrane (Randow and Seed 2001). In a later study, a macrophage-specific Gp96-deficient mouse was created (Yang et al 2007b). Macrophages from these mice developed normally and were responsive to a range of cytokines including: IFN-γ, TNF-α and IL-1β.…”
Section: Gp96mentioning
confidence: 99%
“…92 Gp96 binds to and activates monocytes and neutrophils, and is essential for the subcellular localization of Toll-like receptors (TLR). 93 Therefore, in addition to promote cell invasion, the interaction of Vip with Gp96 could possibly interfere with TLR trafficking, leading to the control of the innate immune response by L. monocytogenes. 92 The aut gene was identified by comparative genomics and encodes Auto, a surface-associated GW repeat-containing protein that is absent from non-pathogenic L. innocua.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%